Management System for Body Distance - Cutanto, Danielo Artono (Wasit Journal of Computer and Mathematics Science, 2022)
Today’s the developing world shows various adventures in every field. In each field the small requirements are very essential to develop big calculations. By using different sources, we can modify it as our requirements and implement in various field. In earlier days the measurements are generally occur through measuring devices. But now a day’s digitalization as is on height. Therefore, we use a proper display unit for measurement of distance. We can use sources such as sound waves which are known as ultrasonic waves using ultrasonic sensors and convert this sound wave for the measurement of various units such as distance, speed. This technique of distance measurement using ultrasonic in air includes continuous pulse echo method, a burst of pulse is sent for transmission medium and is reflected by an object kept at specific distance. The time taken for the sound wave to propagate from transmitter to receiver is proportional to the distance of the object. In this distance measurement system, we had ultrasonic sensor HC-SR04 interfaced with arduino Uno R3. Programming and hardware part of ultrasonic sensor interfacing with arduino Uno R3.
Keywords: Arduino, Uno R3, Body distance, Ultrasonic